Enhanced mitigation in nutrient surplus driven by multilateral crop trade patterns - Hongwei Lu; Wei Feng; Pengdong Yan; Jiajie Kang; Chunfang Jiang; Qing Yu; Tianci Yao; Yuxuan Xue; Dongzhe Liang; Yiming Yan (Communications Earth & Environment, 2022)
Multilateral crop trading that maximizes the system benefit and minimizes the inequality level of water-land benefits could effectively mitigate both nutrient surplus and footprint, according to an integrated evaluation model for China and central Asia.